Multimodality Management of Complex Periorbital Venolymphatic Malformations. Issue 4 (July 2019) - Ramesh, Sathyadeepak; Duckwiler, Gary; Goldberg, Robert A.; Rootman, Daniel B.
Abstract : Purpose: To review a representative case series and share a stepwise approach to the diagnosis and treatment of periorbital venolymphatic malformations. Methods: A case series of 9 patients with representative periorbital venolymphatic malformations. All patients managed at the University of California, Los Angeles Orbital Center for a vascular malformation over the last 5 years were reviewed. Cases representative of the varied pathologic findings and techniques were selected. The clinical, radiologic, and intraoperative findings are presented and a survey of techniques composed. Results: Venolymphatic malformations can have protean manifestations. Characteristics vital to the understanding and management of these lesions are the classification and vascular composition of the lesion, internal flow and drainage patterns, anatomic localization and association with distant components. Options for treatment include sclerotherapy, biologic therapy, embolization, surgical excision, or some combination thereof. Conclusions: A comprehensive understanding of each patient's unique lesion is critical to a rational treatment approach. Teamwork and creativity are key to effectively managing these lesions. Abstract : Thorough understanding and a creative approach are necessary for definitive management of periorbital venolymphatic malformations.Supplemental Digital Content is available in the text.